2020
DOI: 10.1002/chem.202003623
|View full text |Cite
|
Sign up to set email alerts
|

CO2‐Enabled Cyanohydrin Synthesis and Facile Iterative Homologation Reactions**

Abstract: Thermodynamic andk inetic control of ac hemical process is the key to access desired products and states. Changes are made when ad esired product is not accessible;o ne may manipulate the reaction with additional reagents, catalysts and/or protecting groups. Here we report the use of carbon dioxide to accelerate cyanohydrin synthesis under neutral conditions with an insoluble cyanide source (KCN) without generating toxic HCN. Under inert atmosphere,t he reaction is essentially not operative due to the unfavore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…At pH 9, both loss of hydroxide from HCO 3 − 1 and loss of water from its conjugate acid, H 2 CO 3 , furnish CO 2 . The latter process is efficiently catalyzed by nucleophiles 18 20 , especially sulfite 21 , so it is unlikely that the otherwise slow kinetics of equilibration limit the photoredox chemistry. Although the equilibrium concentration of CO 2 is very low in a solution containing HCO 3 − 1 at pH = 9 relative to the concentration of 1 ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At pH 9, both loss of hydroxide from HCO 3 − 1 and loss of water from its conjugate acid, H 2 CO 3 , furnish CO 2 . The latter process is efficiently catalyzed by nucleophiles 18 20 , especially sulfite 21 , so it is unlikely that the otherwise slow kinetics of equilibration limit the photoredox chemistry. Although the equilibrium concentration of CO 2 is very low in a solution containing HCO 3 − 1 at pH = 9 relative to the concentration of 1 ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is important to note that the employment of CO 2 can complicate the outcome of reactions due to undesired binding of nucleophiles therefore reducing the reactivity. Based on our investigation and previous studies [15,27,28], we presumed that the positive effects of CO 2 in catalyzing chemical reactions can be general, particularly in reactions involving reversible steps. In the current investigation with chalcones, the reaction is highly controlled by thermodynamics that allowed us to access various products in high yield.…”
Section: Discussionmentioning
confidence: 71%
“…[10] Our recent research on the reaction of cyanides with aldehydes under a CO 2 atmosphere revealed the facile formation of cyanohydrins where a variety of solvents including protic solvents could afford high yields of cyanohydrins. [11] It is important to note here that the cyanide addition reactions are often sluggish and unselective, however, can be accelerated with the use of CO 2 (Scheme 2). [12] This led us to invert our focus and measure the ability of aldehydes and CO 2 to remove cyanide from water as a method of purification.…”
mentioning
confidence: 99%
“…While the equilibrium typically favors the aldehyde under neutral pHs, we previously found that in the presence of CO 2 the equilibrium is shifted towards the cyanohydrin. [11] This is exemplified by benzaldehyde which is efficiently converted to benzaldehyde cyanohydrin (mandelonitrile) by the reaction with NaCN in water under a CO 2 atmosphere (1 atm). Mandelonitrile was separated from the aqueous phase, allowing for easy isolation of the aqueous phase.…”
mentioning
confidence: 99%
See 1 more Smart Citation